The Manganan Tradition as a Reflection of the Values of Character Education Based on Local Wisdom at the Baitul Aziz Mosque in Kauman Jekulo Kudus - Melinda Puspita; Moh. Rosyid (JURNAL PENDIDIKAN IPS, 2025)
The Manganan tradition preserved at Baitul Aziz Mosque, Kauman, Jekulo, Kudus, is a living expression of local wisdom rich in meaning. More than just communal eating, this tradition serves as a medium to strengthen social bonds and instill character education values. This study aims to explore how the Manganan tradition reflects character education values rooted in local wisdom—such as mutual cooperation, religiosity, togetherness, and gratitude. Employing a qualitative descriptive approach, data were collected through participatory observation, in-depth interviews with community leaders and participants, as well as visual and textual documentation. The findings reveal that the literal meaning of Manganan (“eating”) transcends biological needs, functioning as an expression of gratitude for sustenance. Elements such as the types of food served (e.g., ingkung ayam symbolizing unity), the serving rituals, and accompanying symbols embody noble values internalized through social interaction. The Manganan tradition effectively integrates character education values like responsibility, tolerance, solidarity, and religious devotion, contributing to social harmony. Preserving this tradition not only safeguards cultural heritage but also plays a significant role in strengthening the character of the younger generation within the framework of local wisdom.